Konseling Islam dan Kesehatan Mental Siswa Dalam Mewujudkan Generasi Emas Tahun 2045 di Indonesia - Susana Aditiya Wangsanata; Sucik Rahayu; Jaiz Jamalulalel (Istifkar: Media Transformasi Pendidikan, 2026)
The purpose of this study is to demonstrate the strategic role of Islamic counseling and its relevance to student mental health in Indonesia. The role of Islamic counseling for student mental health is to meet the aspirations of the Indonesian nation to realize a golden generation in 2045. Problems in the field indicate that student mental health problems result in mental disorders such as excessive anxiety and moral degradation that require appropriate treatment. The integration of spiritual values ​​in Islamic counseling is a basic requirement in the national education system as a tangible form of scientific contribution. This qualitative research uses a literature study approach. Primary and secondary data are obtained from reliable scientific sources. Data analysis uses content analysis, which examines the concepts, ideas, and values ​​within the research data sources. The results of this study indicate that the integration of Islamic counseling in maintaining student mental health can be done through the tazkiyatun nafs technique. In addition, it can also strengthen students' piety and resilience. This approach, in practice, only addresses clinical symptoms, where these conditions can build a solid foundation of character by guiding students to realize spiritual awareness. Islamic counseling services have been proven to provide a balance between emotional intelligence and intellectual intelligence. Counseling services are a fundamental and crucial instrument in creating a generation that is mentally and spiritually strong and has ethical dignity, so that it can become a complete golden generation in 2045. The success of this transformation is none other than the power that has synergy between school counselors, curriculum and religious environment.